A global approach for plantar fasciitis with extracorporeal shockwaves treatment - Federico Giordani; Andrea Bernini; Hannes Müller-Ehrenberg; Carla Stecco; Stefano Masiero (PAGEPress Publications, 2019)
Extracorporeal Shockwaves Treatment is considered an effective therapeutic option for plantar fasciitis, but the standard application in the medial insertion of the plantar fascia on the calcaneus has provided ambiguous evidences. In this case, a 63-year man with plantar fasciitis was treated in a 3-session program and Foot and Ankle Outcome Scale and Foot Functional Index questionnaires were chosen for the clinical outcome evaluation. The therapy was focused on the active trigger or myofascial points of the leg, thigh and pelvis in order to return the correct equilibrium of the myofascial system of the whole limb. The patient has already reported an improvement after the second session (FAOS: 76 vs 33, FFI: 85%) which was confirmed in the third one and in the 1-month follow up (FAOS: 79, FFI: 6%) Results suggest that plantar fasciitis may be due to proximal rigidity or tension of the fascia and a global approach using ESWT may have a similar or better outcome respect to the standard application.